Inflasi dalam Perspektif Ekonomi Makro Islam dan Implikasinya terhadap Stabilitas Ekonomi - Aprilia, Tia (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Inflation is a macroeconomic phenomenon that has a significant repercussions on a nation’s economic stability, including a decline in purchasing power, unequal income distribution, and economic uncertainty. In conventional economics, inflation is generally understood as a general and sustained upward movement in the prices of goods and services. Meanwhile, Islamic macroeconomics views inflation not only as a monetary issue but also as a result of deviations from moral values, imbalances between the real and monetary sectors, and economic practices that are inconsistent with the principles of justice and welfare. This article aims to analyze the concept of inflation from an Islamic macroeconomic perspective and the consequences for economic stability. The study adopts a literature review methodology with a descriptive approach-analytical approach to classical and contemporary Islamic economic literature. The results indicate that Islamic economics emphasizes price stability through strengthening the real sector, prohibiting usury, controlling speculation, and the involvement of the state in preserving, economic justice. Thus, the application of Islamic economic principles is expected to minimize inflationary pressures and create sustainable economic stability.